2020
DOI: 10.1002/nme.6519
|View full text |Cite
|
Sign up to set email alerts
|

Computational Morphogenesis: Morphologic constructions using polygonal discretizations

Abstract: To consistently coarsen arbitrary unstructured meshes, a computational morphogenesis process is built in conjunction with a numerical method of choice, such as the virtual element method with adaptive meshing. The morphogenesis procedure is performed by clustering elements based on a posteriori error estimation. Additionally, an edge straightening scheme is introduced to reduce the number of nodes and improve accuracy of solutions. The adaptive morphogenesis can be recursively conducted regardless of element t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Finally, stresses at the Gauss points of each single virtual grid are obtained using the shape functions of the bilinear quadrilateral element. We remark that the patch-based gradient recovery scheme (Choi et al 2021;Chi et al 2019) may be an alternative choice to evaluate the stress field around the crack-tip region, which can provide a more accurate gradient field than the original VEM solutions. A further comparative study of various stress recovery schemes on VEM for fracture modeling is subjected to future investigation.…”
Section: Virtual Grid-based Stress Recovery (Vgsr) In Vemmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, stresses at the Gauss points of each single virtual grid are obtained using the shape functions of the bilinear quadrilateral element. We remark that the patch-based gradient recovery scheme (Choi et al 2021;Chi et al 2019) may be an alternative choice to evaluate the stress field around the crack-tip region, which can provide a more accurate gradient field than the original VEM solutions. A further comparative study of various stress recovery schemes on VEM for fracture modeling is subjected to future investigation.…”
Section: Virtual Grid-based Stress Recovery (Vgsr) In Vemmentioning
confidence: 99%
“…Recently, the virtual element method (VEM) is developed to consistently handle arbitrary polygonal and polyhedral elements (Beira ˜o da Veiga et al 2013). Because of the flexibility on the element shape, VEM has been utilized to solve various engineering problems (Choi et al 2021;Park et al 2019;Chi et al 2020;Wriggers et al 2017Wriggers et al , 2021. For the application to brittle crack propagation problems, a cutting technique is employed on a polygonal mesh (Hussein et al 2019), while some of computational results demonstrated the oscillation in a predicted crack path.…”
Section: Introductionmentioning
confidence: 99%